Gerakan Masyarakat Peduli Kesehatan Tanggap Penggunaan Obat dan Kosmetik yang Aman - Andriani, Medi; Hafsari, Winda Galuh; Putri, Rezky Amelia; Amelda, Mustika Dwi; Almukharomah, Adella; Amelia, Faranita Nur; Oktaniasih, Putri; Oktapiani, Fenti; Kirana, Sahla Tahta; Safitri, Desti Rizkyan (Universitas Baiturrahim, 2025)
Community Service carried out by a group of students in order to advance the welfare of the community and educate the nation's life. This activity was carried out in Mersam Village, Mersam District, Batanghari Regency. It was carried out using the method of providing learning experiences in the form of socialization and counseling that went directly to the community carried out by students and lecturers, carried out within 30 days. The results of several activities that we have carried out are in the activity of checking hypertension and blood sugar health, the results were obtained from 40 people who participated in this activity, who had blood pressure> 120/80 mmHg as many as 6 people, 120 - 129/80 - 84 mmHg as many as 9 people, 130 - 139/85 - 89 as many as 7 people, and> 140/90 mmHg as many as 18 people. And have normal blood sugar levels (>99 mg/dl) as many as 7 people, pre-diabetes (100-180 mg/dl) as many as 21 people, Diabetes (>200 mg/dl) as many as 12 people. This KKN activity has succeeded in increasing the knowledge and participation of Mersam Village residents regarding personal and environmental health, increasing local roles and resources, increasing community independence and welfare as well as knowledge for Mersam Village residents regarding the correct use of drugs and safe cosmetics.